The Effect of Natural Scenery Quality, Public Transportation Availability, and Destination Security on Tourist Satisfaction Level at Mount Bromo, East Java - Dewi, Kemmala; Krisdiyanto, Aris; Setiawati, Rahmi (West Science Interdisciplinary Studies, 2024)
This study investigates the interplay between natural scenery quality, public transportation availability, destination security, and tourist satisfaction level at Mount Bromo, East Java. A quantitative approach utilizing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3 software is employed to analyze survey data collected from 150 tourists visiting Mount Bromo. The results reveal significant relationships between natural scenery quality, public transportation availability, destination security, and tourist satisfaction level. Natural scenery quality emerges as a primary driver of tourist satisfaction, with the breathtaking landscapes of Mount Bromo significantly influencing visitors' overall experiences. Furthermore, the availability and accessibility of public transportation and perceptions of destination security play crucial roles in shaping tourist satisfaction levels. These findings underscore the importance of holistic destination management strategies that prioritize the preservation of natural and cultural assets, the enhancement of transportation infrastructure, and the maintenance of destination security to ensure the sustainable development of Mount Bromo as a premier tourist destination.